2018
DOI: 10.3389/fncel.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

The Spinal Neurons Exhibit an ON-OFF and OFF-ON Firing Activity Around the Onset of Fictive Scratching Episodes in the Cat

Abstract: In a previous report, we found neurons with ON-OFF and OFF-ON firing activity in the obex reticular formation during scratching. The aim of the present study was to examine whether the spinal neurons also exhibit this type of activity in relation to the “postural stage” of fictive scratching in the cat. We found that the extensor and intermediate scratching neurons exhibit an ON-OFF firing rate; conversely, the flexor neurons show an OFF-ON activity, relative to every scratching episode. These patterns of spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In other studies, it was found that previous to the alternating flexor-extensor activity during scratching, a positive DC shift occurs in the hind limb enlargement of decerebrate cats (Bayev and Kostyuk, 1981). Such DC shift is correlated to the tonic activity of interneurons from the deep dorsal horn and to the postural stage that precedes scratching (Cuellar et al, 2018). As stated in our ''Results'' section, we recorded a similar positive DC shift correlated to interneuron activity from the deep dorsal horn.…”
Section: Slow DC Potentialsupporting
confidence: 84%
“…In other studies, it was found that previous to the alternating flexor-extensor activity during scratching, a positive DC shift occurs in the hind limb enlargement of decerebrate cats (Bayev and Kostyuk, 1981). Such DC shift is correlated to the tonic activity of interneurons from the deep dorsal horn and to the postural stage that precedes scratching (Cuellar et al, 2018). As stated in our ''Results'' section, we recorded a similar positive DC shift correlated to interneuron activity from the deep dorsal horn.…”
Section: Slow DC Potentialsupporting
confidence: 84%
“…Our survey of the literature provides two observations: First, a distribution of firing rates across neuronal population has rarely been reported (Petersen and Berg, 2016;Cuellar et al, 2018). Second, those experimental reports that do provide the firing rate distribution, they seem in impressive agreement.…”
Section: Experimentally Observed Firing Rate Distributionsmentioning
confidence: 53%
“…We performed experiments in four adult cats (2.3–3.7 kg, two males and two females). We followed similar experimental procedures as in previous reports from our group (Cuellar et al, 2009, 2018; Pérez et al, 2009; Tapia et al, 2013). During surgery, we induced and maintained deep anesthesia with isoflurane at 2%.…”
Section: Methodsmentioning
confidence: 99%